2021
DOI: 10.3389/fmicb.2021.709517
|View full text |Cite
|
Sign up to set email alerts
|

Non-structural Proteins of Severe Fever With Thrombocytopenia Syndrome Virus Suppress RNA Synthesis in a Transcriptionally Active cDNA-Derived Viral RNA Synthesis System

Abstract: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease caused by the tick-borne SFTS bunyavirus (SFTSV) resulting in a high fatality rate up to 30%. SFTSV is a negative-strand RNA virus containing three single-stranded RNA genome segments designated as L, M, and S, which respectively, encode the RNA-dependent RNA polymerase (RdRp), glycoproteins Gn and Gc, and nucleoprotein (N) and non-structural proteins (NSs). NSs can form inclusion bodies (IBs) in infected and transfected cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…This disease is most prevalent during the summer, and the population is generally susceptible. SFTS virus (SFTSV) is an RNA virus with a single-stranded genome, primarily transmitted through tick bites ( Ren et al, 2021 ). Ticks serve as the main vectors responsible for infecting hosts, including humans, livestock, and wild animals, thereby facilitating the transmission of SFTSV ( Luo et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…This disease is most prevalent during the summer, and the population is generally susceptible. SFTS virus (SFTSV) is an RNA virus with a single-stranded genome, primarily transmitted through tick bites ( Ren et al, 2021 ). Ticks serve as the main vectors responsible for infecting hosts, including humans, livestock, and wild animals, thereby facilitating the transmission of SFTSV ( Luo et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the NSs-TRIM21 interaction-mediated activation of Nrf2 may have a specific role in viral pathogenesis. Moreover, NSs were sufficient to inhibit IFN-β induction by interfering with LSm14A as an activator of IFN regulatory factor3 (IRF3) [ 11 ]. Extracellular IFNs activate Janus kinase–signal transducer and activator of transcription and the phosphoinositide 3-kinase–AKT–mechanistic target of rapamycin pathway, which regulates the expression of autophagy-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…NSs are associated with viral NP and RNA and may be involved in viral RNA replication [ 9 ]. Furthermore, it has been reported that NSs can act as a skeletal protein supporting SFTSV RNA replication, as replication intermediates of viral RNA in the form of NP and dsRNA have been found in VLS [ 10 , 11 ]. The role of NS proteins and their significance in SFTSV RNA replication are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The S segment, containing 1,744 nucleotides, codes for the nucleocapsid protein (N) (29)(30). The M segment, made up of 3,378 nucleotides, is responsible for coding the glycoprotein precursor (GPC) (31). Lastly, the L segment, with 6,368 nucleotides, codes for the RNA-dependent RNA polymerase (RdRp) (32).…”
Section: Severe Fever With Thrombocytopenia Syndromementioning
confidence: 99%
“…The glycoprotein precursor of SFTSV undergoes post-translational cleavage, forming spikes on the surface of the virus. The Gn protein plays a critical role in attaching to the receptors of the host cell, while the Gc protein facilitates fusion with the membranes of the host cell (31).…”
Section: Severe Fever With Thrombocytopenia Syndromementioning
confidence: 99%